Prevalence of Campylobacter subtypes in pheasants (Phasianus colchicus spp. torquatus) in the Czech Republic - M. Nebola; G. Borilova; I. Steinhauserova (Veterinární Medicína, 2007)
At the turn of 2005 and 2006, cecal samples from 302 pheasants, from two flocks from a farm with intensive production, and from 200 wild birds were collected. The prevalence of Campylobacter spp. in the intestinal contents of pheasants from the farm was 70.20%. 50.47% of isolated strains were identified as C. coli and 41.40% as C. jejuni. In samples from wild pheasants, positive cultivation of Campylobacter spp. was proven in 27.5% of cases. A total of 15 PFGE subtypes were noted among the Campylobacter spp. isolates. C. jejuni strains could be divided into 16 fla-RFLP subtypes. No PFGE profile specific for C. jejuni and C. coli, respectively, was found. When comparing wild birds with farmed pheasants, there were eight possible combinations of PCR/RFLP and PFGE subtypes in wild birds and 40 combinations in farmed pheasants. No preferred combination of both subtypes was detected and all combinations were randomly ordered. To determine the significance of pheasants as a source of C. jejuni infection in humans, the RFLP and PFGE patterns of pheasant isolates are currently being compared with those of isolates from diarrheic patients.